Critical Appreciation Learning Design in Examining Political Values in Literary Works - Draditaswari, Silka Yuanti (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Minimal political awareness can have an impact on the quality of student human resources. This is due to students' insensitivity to political methods in society. Students, especially at the intermediate level, who have developed awareness and cognitive richness, are able to accommodate all new knowledge concepts. Political knowledge is very important to know so that they can carry out ideal politics to reach an agreement with their social partners. All political knowledge is reflected in literary works containing Indonesian political history. In fact, there are many literary works with political themes that are interesting to study. Learning critical observation of literary texts is an appropriate model for examining the message of a literary work. With critical observation, students can study with an objective mind and not be pragmatic in assessing a message.